2011
DOI: 10.1002/acp.1643
|View full text |Cite
|
Sign up to set email alerts
|

Effect of viewing the interview and identification process on juror perceptions of eyewitness accuracy

Abstract: This study examined whether showing jurors a video of the witness's initial attempts to describe and identify the perpetrator would facilitate jurors' ability to discriminate between accurate and inaccurate witnesses. Mock jurors observed a simulated trial in which the key witness testified under direct examination and cross-examination. The jurors saw either the witness's testimony or the witness's testimony plus videotape footage of the earlier police interviews in which the witness described and attempted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 34 publications
4
21
1
Order By: Relevance
“…In addition, we sought to investigate how evidence type influenced observer sensitivity and scepticism. We hypothesized the following: Replicating and extending Reardon and Fisher (), we predicted that observers would be more likely to believe eyewitness identifications in the testimony condition than in the identification (ID) condition, with ID+Testimony (presentation of both the identification and testimony videos) falling between the two. In signal detection terms, observers in the testimony condition would have a belief response bias (negative values of c ) that would be reduced or eliminated in the ID+Testimony or ID condition.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, we sought to investigate how evidence type influenced observer sensitivity and scepticism. We hypothesized the following: Replicating and extending Reardon and Fisher (), we predicted that observers would be more likely to believe eyewitness identifications in the testimony condition than in the identification (ID) condition, with ID+Testimony (presentation of both the identification and testimony videos) falling between the two. In signal detection terms, observers in the testimony condition would have a belief response bias (negative values of c ) that would be reduced or eliminated in the ID+Testimony or ID condition.…”
Section: Introductionsupporting
confidence: 85%
“…In signal detection terms, observers in the testimony condition would have a belief response bias (negative values of c ) that would be reduced or eliminated in the ID+Testimony or ID condition. However, we had no basis upon which to predict whether this criterion shift would be so drastic as to produce a disbelief response bias (positive values of c ); that is, scepticism of the eyewitness identifications. In line with Reardon and Fisher (), we predicted a significant Identification accuracy × Evidence type interaction on observers' perceptions of eyewitness accuracy. Specifically, we expected that more observers would believe accurate than inaccurate identifications in the ID and ID+Testimony conditions, but not in the testimony condition.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, our mediation analyses support Reardon and Fisher (2009) who found that participants distinguished between accurate and inaccurate witnesses better after viewing a video of the lineup identification compared with only viewing a witness in court. One explanation for these results is suggested by the participants’ own responses: almost 30% of participants reported using the witness's behaviour at the lineup in their decision‐making process.…”
Section: Discussionsupporting
confidence: 79%
“…Assuming that the original confidence statement is recorded, jurors might learn about the prior statement in one of two ways: through the witness reading the written record of her statement at the time of the identification or through a videotape of the actual identification procedure. Although experts have recommended videotaping identification procedures for some time (e.g., Kassin, 1998; Sporer, 1992, 1993; Wells et al , 1998) and an increasing number of jurisdictions have adopted such procedures (Wells, 2006), extant research on videotaped lineup procedures only focuses on whether exposure to the videotaped procedure can help jurors discriminate between accurate and inaccurate eyewitnesses (e.g., Kassin, Rigby, & Castillo, 1991; Lindholm, 2008; Reardon & Fisher, 2009). We do not yet know how videotaped identification procedures will affect evaluations of confidence inflation evidence.…”
Section: Introductionmentioning
confidence: 99%
“…In both studies, one group of participants witnessed a staged crime and made identifications from a lineup and another group of participants, that is, mock jurors, judged the accuracy of those identifications. Reardon and Fisher (2011) found that mock jurors were better able to discriminate between correct and incorrect identifications when they were presented with a video recording of the identification along with the witness's testimony than when they were presented with the witness's testimony alone. In contrast, Beaudry et al (2013) concluded that the opportunity to view a video recording of the identification did not improve mock juror's ability to distinguish between correct and incorrect identifications.…”
Section: Videotapingmentioning
confidence: 99%